Korelasi Temuan Limfosit Plasma Biru dengan Kadar C-Reaktif Protein sebagai Penunjang dalam Diagnosis Demam Berdarah Dengue - Sholihah, Ayu Safitri; Danuyanti, I Gusti Ayu Nyoman; Zaetun, Siti; Ariami, Pancawati; Resnhaleksmana, Ersandhi (Faculty of Medicine, Universitas Andalas, 2022)
Dengue Hemorrhagic Fever diagnosis is supported by examining Blue Plasma Lymphocytes and C-Reactive Protein, in which Blue Plasma Lymphocytes can distinguish Dengue and Non-Dengue infections. At the same time, the C-Reactive Proteins are used to see the presence of inflammation due to infections such as Dengue Virus infection. Objectives: To analyzed the correlation of the number of Blue Plasma Lymphocytes with C-Reactive Protein (CRP) levels in Dengue Hemorrhagic Fever patients. Methods: This study was analytical observational research with a cross-sectional design. The sample used was a patient diagnosed with DHF with a positive Nonstructural protein 1 (NS1) or Rapid Diagnostic Test (RDT) IgG/IgM result. The data was collected and analyzed using Spearman's rank statistical test. Results: The average number of Blue Plasma Lymphocytes in positive samples was 8%, with the number of negative results, namely 4 (13.33%) samples and 26 (86.67%) samples with positive Blue Plasma Lymphocyte results. The average level of C–Reactive Protein in the positive samples was 29.36 mg/L, with results that had normal levels were 11 (36.67%) samples and 19 (63.33%) samples with abnormal C-Reactive Protein levels. Spearman's Rank statistical test results obtained a value of p = 0.000 < 0.05, indicating a correlation between the number of Blue Plasma Lymphocytes and C–Reactive Protein levels in Dengue Hemorrhagic Fever patients. Conclusion: The more Blue Plasma Lymphocytes, the higher C–Reactive Protein levels in Dengue Hemorrhagic Fever.Keywords: blue plasma lymphocytes, C–reactive protein, dengue hemorrhagic fever